(3WQI GdSdes - (3eMfU HGH Hf CYHjO GdOjeGfj,J (B1277 (3g` s ((3eMeO Hf eMfV Hf CMeO Hf Hhce s)
(3ChdgG (B:s
(3GdMeO ddg GdPi bO CNQLG fJGFL GdacQ dCQHGH GdMLG hMX Yfge ef SeGA GdYbd cd MLGH ef SMGH GdLgd s
(3BNQgG (B:s
(3hbO GfJgi HMeO QH Gdadb eGQ efg ef af Yde GdefWb GdCNVQi YGHO GdQMef GdeQJLi ef QHg GdefGf eGbUWYJ TeS GdfgGQ CHQLG hWdY GdHOQ ai GdYLG s
(3GdYfGhjf hGdahGUd HGdMeQIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs